1989
DOI: 10.2105/ajph.79.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Television viewing and obesity in adult males.

Abstract: We estimated the extent to which time spent watching television is associated with obesity and super-obesity among 6,138 employed adult males. After adjustment for age, smoking status, length of work week, measured physical fitness, and reported weekly hours of exercise, people who viewed TV more than three hours/day were twice as likely to be obese as those who viewed less than I hour/ day. Those who viewed for I to 2 hours daily had a relative risk of 1.60 (1.21, 2.11). Physical fitness consistently confound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 8 publications
7
69
0
1
Order By: Relevance
“…24 However in this study the relationship between television viewing and overweight was modi®ed by physical activity; a ®nding consistent with other cross-sectional studies that have found physical activity or physical ®tness to modify this relationship. 21,22 Our study has produced mixed results, in that there was a lack of a clear relationship between overweight and television viewing for the most sedentary category but a relationship appeared to exist for other activity categories. This suggests that some active people may compensate for their participation in physical activity by increased nutritional intake or increased sedentary periods in other parts of their day.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…24 However in this study the relationship between television viewing and overweight was modi®ed by physical activity; a ®nding consistent with other cross-sectional studies that have found physical activity or physical ®tness to modify this relationship. 21,22 Our study has produced mixed results, in that there was a lack of a clear relationship between overweight and television viewing for the most sedentary category but a relationship appeared to exist for other activity categories. This suggests that some active people may compensate for their participation in physical activity by increased nutritional intake or increased sedentary periods in other parts of their day.…”
Section: Discussionmentioning
confidence: 75%
“…9±12,14,16,17,20 Fewer studies have examined the relationship between overweight and obesity, television viewing, and physical activity in adults. One study of adult males 21 and another of adult females, 22 found signi®-cant positive associations between body fat percentage and hours of television viewing. A positive association between television viewing and BMI was reported among adult Pima Indians, together with a negative relationship between television viewing and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…278 -280 In some reports, television viewing and other sedentary activities have also been related to increased body weight, 281,282 although more of the evidence relates to children. 283,284 Deficient expenditure of energy could occur not only from sedentary lifestyles, but also from physiological changes that occur with aging.…”
Section: Achieving Energy Balance In Populationsmentioning
confidence: 99%
“…There are at least 2 explanations for the observed positive association between TV watching and diabetes risk. First, TV watching is directly related to obesity and weight gain, [11][12][13][14][15]33 probably due to lower energy expenditure (ie, less physical activity) and higher caloric intake. Second, participants who spent more time watching TV tended to eat more red meat, processed meat, snacks, refined grains, and sweets and fewer vegetables, fruits, and whole grains.…”
Section: Commentmentioning
confidence: 99%